2015
DOI: 10.1097/mib.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity, Intima Media Thickness, and Flow-mediated Dilatation in Patients with Normotensive Normoglycemic Inflammatory Bowel Disease

Abstract: Article first published online 23 March 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 42 publications
(60 reference statements)
4
66
1
3
Order By: Relevance
“…The association between disease duration, a variable associated with chronic inflammation, and increased arterial stiffness in patients with UC is in accordance with previous data [11,12,28,29]; the association between acute inflammation and arterial stiffening has been previously reported in other models of inflammation [30]. Taken together, these findings suggest that, in contrast to physiological aging and accelerated aging reported in patients with CKD, in whom aortic, but not brachial stiffening was shown, in UC patients both elastic and muscular components of arterial tree could be affected by inflammation.…”
Section: Arterial Phenotype In Patients With Ucsupporting
confidence: 80%
“…The association between disease duration, a variable associated with chronic inflammation, and increased arterial stiffness in patients with UC is in accordance with previous data [11,12,28,29]; the association between acute inflammation and arterial stiffening has been previously reported in other models of inflammation [30]. Taken together, these findings suggest that, in contrast to physiological aging and accelerated aging reported in patients with CKD, in whom aortic, but not brachial stiffening was shown, in UC patients both elastic and muscular components of arterial tree could be affected by inflammation.…”
Section: Arterial Phenotype In Patients With Ucsupporting
confidence: 80%
“…Ozturk et al found significant increase in PWV in a rather large sample but they were not able to evidentiate a difference in IMT [31]. In our study, we assessed arterial stiffness, not only by PWV, but also by central AIx.…”
Section: Discussionmentioning
confidence: 59%
“…Though being effective in the maintenance of remission of mild-to-moderate UC and possibly effective in chemoprevention, in other indications the role of 5-ASA is questioned and definitely not enough for the proper control of inflammation in Crohn's Disease. The effect of medications on vascular parameters has not been confirmed by Ozturk et al [31] though this could be explained by a more relevant proportion of UC patients in their cohort, thus on maintenance therapy with 5-ASA, which in UC could lead to an adequate control of inflammation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For these abnormalities, noninvasive vascular parameters are used. Flow-mediated dilatation is used for endothelial dysfunction and carotid femoral pulse wave velocity as a marker of arterial stiffness [22]. CIMT is a vascular parameter of structural alterations in intima and media in early atherosclerosis [23].…”
Section: Discussionmentioning
confidence: 99%